Differences in SARS-CoV-2 Vaccine Response Dynamics Between Class-I- and Class-II-Specific T-Cell Receptors in Inflammatory Bowel Disease - Xu, Alexander M.; Li, Dalin; Ebinger, Joseph E.; Mengesha, Emebet; Elyanow, Rebecca; Gittelman, Rachel M.; Chapman, Heidi; Joung, Sandy; Botwin, Gregory J.; Pozdnyakova, Valeriya; Debbas, Philip; Mujukian, Angela; et al. (Frontiers in Immunology, 2022)
Over the course of the COVID-19 pandemic, vulnerable populations such as the immunocompromised were identified, vaccinated, and heavily monitored. Remarkably, one group of the immunocompromised – patients with inflammatory bowel disease (IBD) – mounted vigorous immune responses to vaccines, comparable to healthy individuals. How these patients, who experience strong immunomodulatory treatments such as anti-TNF stimulation, respond to the vaccine is unknown. Here we used T-cell receptor sequencing to show that T-cell responses in an IBD cohort were influenced by demographic and immune factors, relative to a healthy cohort of health care workers (HCWs). Blood samples were longitudinally collected around vaccination timepoints, and the TCR Vβ gene repertoires were sequenced and analyzed for COVID-19-specific clones. We observed significant age and vaccine type differences in the overall strength of the T-cell response. We further stratified the T-cell response into Class-I- and Class-II-specific responses, showing that traditional vaccines induced Class-I-biased T-cell responses and mRNA vaccine types led to differential responses, with Moderna’s mRNA-1273 vaccine inducing a more Class-I-deficient T-cell response. Finally, we showed that these T-cell patterns were consistent with antibody serology from the same patients. Our results account for the surprising success of vaccination in nominally immuno-compromised IBD patients, while suggesting vaccination guidelines for IBD patients prone to deficiencies in T-cell response.